2015
DOI: 10.1002/14651858.cd006447.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for assisting the induction of anaesthesia in children

Abstract: This review shows that the presence of parents during induction of general anaesthesia does not diminish their child's anxiety. Potentially promising non-pharmacological interventions such as parental acupuncture; clowns/clown doctors; playing videos of the child's choice during induction; low sensory stimulation; and hand-held video games need further investigation in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
193
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(200 citation statements)
references
References 80 publications
2
193
0
5
Order By: Relevance
“…If effective, this method would help to reduce PA in children, even in those PHs with reduced staff and economic resources, and would allow a higher number of children to receive effective nonpharmacological interventions to reduce PA. Nonpharmacological interventions improve children's cooperation 43 and contribute to containing health costs, 44,45 as they are usually cheaper than medications. Also, some nonpharmacological interventions are as effective as drugs in reducing PA 22 ; therefore, their use may help to avoid the adverse effects of some medications.…”
Section: Discussionmentioning
confidence: 99%
“…If effective, this method would help to reduce PA in children, even in those PHs with reduced staff and economic resources, and would allow a higher number of children to receive effective nonpharmacological interventions to reduce PA. Nonpharmacological interventions improve children's cooperation 43 and contribute to containing health costs, 44,45 as they are usually cheaper than medications. Also, some nonpharmacological interventions are as effective as drugs in reducing PA 22 ; therefore, their use may help to avoid the adverse effects of some medications.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies used the same methods of distraction, such as magic tricks, music, funny stories, funny songs, telling jokes and puppets. Over half of study reported that the clown's intervention took less than 15 minutes in one intervention [3,4,8,12,15,16,21,22,25,[27][28][29][30][31][32][33]. Again, it is of the utmost importance to get more homogeneity in the type of intervention and duration to improve the knowledge and the efficacy of the clown's intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011 the European federation of hospital clowns was founded [6]. Previous reviews reported the effects of clown hospital on anxiety and pain but there was no comprehensive review of studies methodical design which assessed benefits of hospital clowning interventions [3,7,8]. The aim of this literature review is to analyze design of the studies, relating to the benefit of hospital clown interventions for hospitalized children.…”
Section: Introductionmentioning
confidence: 99%
“…Many non-pharmacological interventions were investigated. Manyande demonstrated the effects of non-pharmacological interventions in assisting the induction of anesthesia in children for reducing their anxiety, distress or increasing their co-operation [5]. They concluded that the presence of parents during induction of pediatric anesthesia did not diminish the child's anxiety.…”
Section: Video Assisted Induction Group In Each Groupmentioning
confidence: 99%